Optimasi Pengambilan Keputusan Material Signage di PT XYZ dengan AHP-TOPSIS - Marlina; Nurhidayat, Asep Endih; Putri, Famelga Clea (Universitas Muhammadiyah Sorong, 2024)
XYZ company in the field of signage design consulting services has product output in the form of the best design recommendations. Output recommendations in design include material selection. However, several times it was found that the recommended materials were not appropriate, such as signage being corrosive. This is because there are factors that are not taken into consideration when making decisions. Factors influencing material selection and a list of material alternatives were identified by conducting interviews with experts who were directly involved in decision making. This research uses the AHP method (Analytical Hierarchy Process method) and TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) and is assisted by Super Decision software. This research uses the AHP method (Analytical Hierarchy Process method) and TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) and is assisted by Super Decision software. The research results show that there are 6 main criteria used in selecting signage making materials, namely, price, quality, availability, durability, ease of processing and processing speed. Weighting using AHP produces an order of importance for each criterion from highest to lowest, namely availability (0.2269), processing speed (0.2216), durability (0.2182), ease of processing (0.1519), quality (0.0919) and price (0.0895). The results of data processing using TOPSIS show that acrylic has the greatest preference for use as a material for making signage with a weight of 0.6569. The research results can be used as a reference for decision making in selecting signage materials with a measurable process.